2018 IEEE 7th World Conference on Photovoltaic Energy Conversion (WCPEC) (A Joint Conference of 45th IEEE PVSC, 28th PVSEC &Amp 2018
DOI: 10.1109/pvsc.2018.8547334
|View full text |Cite
|
Sign up to set email alerts
|

Potential Analysis of a Rear-Side Passivation for Multi-Junction Space Solar Cells based on Germanium Substrates

Abstract: For future 4-junction Ge based multi-junction solar cells, the current generated in the Ge sub-cell gets very important. We developed an efficient rear-side passivation stack, which results in minority carrier lifetimes (τ eff ) ≈ 200 µs and investigated its performance in an accelerated aging experiment (1 MeV electron irradiation). The aging caused a strong lifetime decrease down to τ eff = 4 µs, whereas the carrier mobility stayed constant. These experimental values provide the basis for Beginning-of-Life a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…> REPLACE THIS LINE WITH YOUR PAPER IDENTIFICATION NUMBER (DOUBLE-CLICK HERE TO EDIT) < 8 120 which shows a plateau of 140 s for n av = 10 14 -10 15 cm -3 which is the estimated n av range used in the lifetime mapping [30]. This good agreement demonstrates the validity of  eff (n av ) measurements using QSS-PC technique on c-Ge samples.…”
Section: Validation Of the Lifetime Measurementssupporting
confidence: 55%
“…> REPLACE THIS LINE WITH YOUR PAPER IDENTIFICATION NUMBER (DOUBLE-CLICK HERE TO EDIT) < 8 120 which shows a plateau of 140 s for n av = 10 14 -10 15 cm -3 which is the estimated n av range used in the lifetime mapping [30]. This good agreement demonstrates the validity of  eff (n av ) measurements using QSS-PC technique on c-Ge samples.…”
Section: Validation Of the Lifetime Measurementssupporting
confidence: 55%
“…In principle, a lower DB is also expected for lower doped Ge substrate and therefore for the LFC sample. However, simulations have shown that an optimized passivation can compensate the loss in DB due to a lower doping level [9]. Therefore, the difference in DB and "B between the standard and the LFC sample in Figure 3 are attributed to a good, but sub-optimal back side passivation.…”
Section: Electrical Characterizationmentioning
confidence: 98%
“…In a recent work, a new design of MJ solar cell with a back mirror and point electrical contacts has shown superior Ge bottom cell performance [9]. This design was also predicted to reduce the operating temperature of the cell by reflecting the unused near infrared solar photons [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…On test samples we showed good passivated Ge surfaces leading to effective minority carrier lifetimes of τ eff > 300 μs on Ge with a doping level of 2 × 10 16 at.cm −3 [9]- [11] as well as ohmic, low resistance contacts. For this article, the developed rear side structure was implemented into a III-V multijunction (MJ) solar cell process.…”
Section: A Sample Descriptionmentioning
confidence: 85%
“…The development and the performance of the passivation layer and the simulated cell potential were described earlier [9]- [11]. Furthermore, the improved rear side was recently integrated successfully into a four junction solar cell device [6].…”
Section: Introductionmentioning
confidence: 99%